IMPLEMENTASI PROGRAM CSR PT. INDO MURO KENCANA DI KABUPATEN MURUNG RAYA, PROVINSI KALIMANTAN TENGAH - Erika Septiani Theresia; Hafizianor Hafizianor; Trisnu Satriadi; Danang Biyatmoko (Universitas Lambung Mangkurat, 2023)
PT. Indo Muro Kencana is one of the companies in Murung Raya Regency that does business in gold and silver mining. PT. Indo Muro Kencana has been conducting CSR programs since it started operating in villages around the company's area, currently focusing more on community development and empowerment (PPM) program activities. There is a village position that increases every year, but there is also a village position that is still the same every year, even though the village has received a CSR program from PT. IMK. Opening the phenomenon of social responsibility that has been implemented by PT. Indo Muro Kencana in these assisted villages later became the principle of implementing this research. The objectives of this study are: analyzing the implementation, analyze the suitability of the preparation, and analyzing the impact of the implementation of PT. Indo Muro Kencana. The research sites include Mangkulisoi Village, Tanah Siang District, Tumbang Bantian Village, Sungai Babuat District, Dirung Lingkin Village, Tanah Siang Selatan District, and Mangkahui Village, Murung District. The data were analyzed using the Interaktive Model analysis method: data collection, reduction, data presentation, and conclusion making. Implementation of CSR PT. IMK through the PPM program is very positively felt by village communities around the mining area, as can be seen through the calculation of the results of the questionnaire distributed to the communities who were respondents in this study, 3.77% stated that the implementation of PT. IMK's CSR program was very good. IMK through the PPM program and 45.59% stated that it was good, 44.53% said it was quite good, 3.64% said it was not good and only 2.47% said it was very bad. Furthermore, public perception of the implementation of the PPM program by CSR PT. IMK can be seen through the calculation of the IPS (Social Acceptance Index) of rural communities as beneficiaries of PPM CSR PT. IMK obtained a score of 59.63% in a moderate position and a Community Behavior Index towards the implementation of PT's CSR PPM program. IMK is at a score of 66.64% moderate position. This shows that the community is quite beneficial and quite accepting of the implementation of PT. IMK through this PPM program.